Impact of deposit insurance on banking stability : a study of developed countries and economies with well-liberalized financial systems - Lim, Wayne Sze Meng (2008)
This paper analyzes the impact of deposit insurance on banking system stability in countries with different levels of economic development and various degrees of financial liberalization.